Study of intrapopulation variability of duration and thermal norms of development of the linden bug Pyrrhocoris apterus (Heteroptera, Pyrrhocoridae) - Balashov, S V; Kipiatkov, V E (Žurnal ėvolûtsionnoj biohimii i fiziologii, 2008)
The existence of significant variability in duration and temperature norms of development has been shown for the first time between families within insect populations. This variability is infer-family and therefore has genetic basis. Revealed for the first time is the statistically significant positive correlations between the regression coefficient of the rate of development for temperature and the threshold of temperature for development of eggs and larvae from different families. The greater the slope of the regression line of the development rate for temperature, the higher the temperature threshold value in this particular family. These results demonstrate for the first time existence of genetic covariation between the regression coefficient and the temperature threshold within the insect populations. It is suggested that the intrapopulational genetic variability in the development time, regression coefficient, and the temperature threshold for development, which is the subject of natural selection, might be the source of the interpopulation and interspecies variability of the temperature reaction norms of development. It was found that value of the linear regression coefficient of development rates for temperature were statistically significantly higher, while the temperature threshold values--lower in eggs as compared with the corresponding parameters in larvae. These results obviously are in contradiction with the concept of the "developmental rate isomorphy in insects and mites" (Jarosik et al., 2002) which claims that the temperature threshold for development should be the same for all species cycle stages, so that only slopes of the regression lines can differ. Shown for the first time was the absence of genetic co-variability of the temperature reaction norms for development of different life cycle stages, i. e., eggs and larvae. This means that the regression coefficient (as well as the temperature requirement of the sum of the degree-days) and the temperature threshold for development in eggs and larvae are inherited independently and thereby they can change in evolution independently according to specific environmental condition under which these life cycle stages exist.